EIGEDOM RIGHTS AS A PERFECT GUARANTEE OF INDIVIDUAL RIGHTS TO OWNERSHIP - Mauliana, Awanda Luthfia Dwi; Handoyo, Dede Sidiq; Zahra, Syifa Amalia; Erowati, Eti Mul; Pudyastiwi, Elisabeth (Judge : Jurnal Hukum, 2025)
Eigendom, derived from Dutch, means "ownership" and refers to the right to control and manage both tangible and intangible assets. In Western legal systems, eigendom is regulated by civil law, granting absolute ownership. In Indonesia, the Civil Code recognizes eigendom as the highest form of ownership, giving owners full freedom to enjoy and manage their assets while adhering to regulations. A clear understanding of eigendom is crucial for legal certainty in property transactions and maintaining economic and social stability. This study employs a normative legal approach to analyze eigendom regulations in Indonesia and compare them with ownership concepts in other countries. An empirical approach is also used through literature studies and interviews with legal practitioners, notaries, and land officials. The data were analyzed using content analysis and presented in comparative tables and diagrams. The study found that eigendom rights in the Civil Code provide strong ownership guarantees but face challenges, particularly in verifying and validating ownership documents, influenced by colonial-era legacies. Comparisons with legal systems in other countries highlight interpretative differences, indicating the need for stricter verification to prevent misuse of rights and illegitimate claims. Although eigendom ensures strong legal protection for property ownership, the study concludes that regulatory improvements are necessary to promote fairness and transparency. The combination of normative and empirical approaches offers a comprehensive view of eigendom rights and emphasizes the urgency of legal reforms for justice in modern property law in Indonesia